SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-3405
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Flying Robotics in Space Missions

Abstract: The Columbia Accident Investigation Board issued a major recommendation to NASA. Prior to return to flight, NASA should develop and implement a comprehensive inspection plan to determine the structural integrity of all Reinforced Carbon-Carbon (RCC) system components. This inspection plan should take advantage of advanced non-destructive inspection technology. This paper describes a non-intrusive technology with a micro-flying robot to continuously monitor inside a space vehicle for any stress related fissures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Power MEMS [14] is a rapidly growing field describing microsystems which generate power or pumped heat. Another area generating lot of interest is the design of micro flying robots [15]. Despite significant interest in applications at small scales not much data exists, either experimental or numerical, at extremely low Re.…”
Section: Introductionmentioning
confidence: 99%
“…Power MEMS [14] is a rapidly growing field describing microsystems which generate power or pumped heat. Another area generating lot of interest is the design of micro flying robots [15]. Despite significant interest in applications at small scales not much data exists, either experimental or numerical, at extremely low Re.…”
Section: Introductionmentioning
confidence: 99%
“…Such a system is portable and integrates several processes that are performed in the laboratory to analyze and evaluate the samples and miniaturize them into a single device [16,17]. Furthermore, several successful research results have also been presented in the field of robotics based on miniaturized sensors and activators [18,19]. Recently, several studies on miniaturization in the power grids have been demonstrated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…[10] Miniaturized robots are often designed and built for tasks that are monotonous or even dangerous for people, including routine manufacturing [11] and space exploration. [12] However, despite all efforts, it has remained elusive to create any useful system-engineered robot on the submillimeter scale. The true challenge resides in the monolithic integration of multiple heterogeneous microcomponents into a flexible or even soft 3D robotic shell.…”
Section: Introduction To the Field: Coming From The Top And Going Downmentioning
confidence: 99%